GAMING MEETS ACCOUNTING: AN INSIGHTFUL JOURNEY THROUGH DORAEMON STORY OF SEASON - Oktaviani, Siska Aprilia (Universitas Negeri Yogyakarta, 2024)
This research explores the educational potential of Doraemon Story of Seasons, a game that blends the charm of the Doraemon series with engaging farming simulation mechanics. The study adopts an ethnographic approach, focusing on participant observation to analyze how the game implicitly teaches fundamental accounting principles. The purpose of this research is to investigate the game's capacity to transform traditional gameplay into an interactive learning environment. Through managing resources, making financial decisions, and engaging in-game economic activities, players interact with core concepts of accounting, such as budgeting investment, and financial tracking. Findings indicate that Doraemon Story of Seasons effectively integrates educational content within its gameplay, providing players with practical experience in financial management and decision-making. The novelty of the study lies in its demonstration of how seemingly conventional video games can serve as an innovative educational tool. This research underscores the transformative potential of game-based learning, suggesting that video games like Doraemon Story of Seasons can be potent platforms for delivering educational content, thus redefining the landscape of learning methodologies. The study opens avenues for further exploration into the use of video games as a viable and effective medium for education. Keywords: Education, Accounting Education, Gamification, Game based Learning, Gaming Accounting